Uma construção histórica do curso de licenciatura em matemática da Universidade Federal de Rondônia Campus Ji-Paraná - Candido, Lenilson Sergio [UNESP] (2015)
The implementation of educational programs at all levels involve both administrative based and didactical-pedagogical based decisions. In this study we aim at understanding the role of each of those types of motivation/justification, in the constitution of a particular teacher education course in Mathematics, at the Ji-Paraná campus of UNIR (Federal University of Rondônia, north of Brazil). Together with official documents, we consider the transcription of interviews with the main actors in the process of implementation and posterior changes in the course. In particular, we approach the case of two Algebra disciplines